EFFECT OF ORAL ADMINISTRATION OF CARBARYL IN THE BLOOD OF GOATS - Anwar, Nudrat; lllahi, Afzal; Sheikh, Abdus Salam; Akbri, M. Zamir Ahmad; Chaudhry, Zafar Ali (Journal of Ayub Medical College Abbottabad, 1989)
ABSTRACT A dose of 2mg/kg body weight was fed to the goats. The results of weekly morning and evening samples of milk, urine and faeces showed that Carbaryl was present in all these excretions, and its amount progressively increased with the passage of time. Growth rate of goats was affected as there was significant decrease in the body weight of experimental goats as compared to control however no significant change was observed in body pH. Carbaryl is an insecticide having the following formula: N-methyl, 1-nephthyl, 1-carbamate (Carbaryl) C 1 2H 1 1 O 2N